2013
DOI: 10.1186/2193-1801-2-623
|View full text |Cite
|
Sign up to set email alerts
|

A study of the controlled degradation of polypropylene containing pro-oxidant agents

Abstract: Intentional degradation by pro-oxidant agents, many of which are metal-based, can result in uncertainty as to the time of biodegradation. Polyacetal (POM) is a thermoplastic polymer commercially classified as an engineering polymer and contains carbon, hydrogen and oxygen. The depolymerization of POM during processing can enhance thermal decomposition. The aim of this study was to investigate the controlled degradation of polypropylene induced by the degradation of POM or d2w®. Mixtures of polypropylene contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…The opposite behavior was observed in OOT and DSC analyses, where pure HDPE showed greater stability. A similar behavior was observed for d2w ® -additivated polypropylene in a study by Carvalho et al [17], using OIT (oxidation induction time), MFI (melt flow index), FTIR and mechanical tests and TG techniques to determine Ea.…”
Section: Crystallinity % 100mentioning
confidence: 63%
See 2 more Smart Citations
“…The opposite behavior was observed in OOT and DSC analyses, where pure HDPE showed greater stability. A similar behavior was observed for d2w ® -additivated polypropylene in a study by Carvalho et al [17], using OIT (oxidation induction time), MFI (melt flow index), FTIR and mechanical tests and TG techniques to determine Ea.…”
Section: Crystallinity % 100mentioning
confidence: 63%
“…Roy et al [17] determined the lifetime of LDPE (taken as the time for 5% mass loss) additivated with cobalt stearate as a prodegradant agent. The additive was directly incorporated into LDPE during extrusion, without a masterbatch, that is, without the influence of the stabilizer load, which are normally used in masterbatches.…”
Section: Crystallinity % 100mentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, the polymers become vulnerable to microorganisms. [2][3][4][5][6] Oxo-biodegradable technology is widely used for agricultural and food packaging applications. [7][8][9][10][11] Several studies have demonstrated that a complex combination of environmental factors including temperature, sunlight, oxygen and microbial activity are responsible for degradation of both polyethylene (PE) and oxo-biodegradable PE.…”
Section: Introductionmentioning
confidence: 99%
“…The degraded samples also exhibited a reduction of crystallinity and melting temperature due to the formation of thinner crystallites and had faster biotic degradation. Carvalho also reported the use of polyacetal as pro‐oxidant to stimulate the oxidation of PP at a concentration of >3 wt%. However, as mentioned above, care and control during fragmentation is needed to avoid environmental hazards associated with the pro‐oxidants.…”
Section: Introductionmentioning
confidence: 99%